Pemberdayaan Masyarakat Melalui Optimalisasi Lahan Pekarangan di Desa Gunungsari Kabuapten Lombok Barat - Muhammad Yamin; Khairuddin; I Wayan Mertha; Andra Ade Riyanto; Ade Andriyan (Universitas Mataram, 2026)
Gunungsari Village, West Lombok Regency, possesses significant agricultural potential; however, household yard utilization remains suboptimal. This community service program aimed to enhance community capacity through training and mentoring in vegetable, mushroom, and catfish cultivation based on household yard optimization. The program applied an andragogical and participatory approach emphasizing 85% practical activities. Results indicate improved knowledge and technical skills in vertical farming, hydroponics, aquaponics, and small-scale catfish cultivation. The program strengthened household food security, reduced food expenditure, and created additional income opportunities. The integrated yard-based cultivation model demonstrates strong potential for sustainability and replication in similar rural contexts.